Pengembangan Rumah Desa Sehat Dengan Implementasi Sistem Informasi Gizi Keluarga (SIGA) - Gamasiano Alfiansyah; Mudafiq Riyan Pratama; Selvia Juwita Swari; Ria Chandra Kartika; Irene Ratri Andia Sasmita (Indonesian Journal Publisher, 2023)
The Ministry of Villages, Development of Disadvantaged Regions, and Transmigration establishes Healthy Village Homes (RDS) in every Village in the Regency and City where stunting prevention is prioritized. Based on the preliminary survey, the implementation of RDS activities in Kemuning Lor Village was not going well so that it had an impact on stunting and other nutritional problems in the village. The purpose of this community service activity was to implement a Family Nutrition Information System (SIGA) in RDS that could be used by the community for early detection of stunting and other nutritional problems. This activity was attended by 24 participants consisting of village officials, RDS managers, and communities with toddlers. The activity phase included a preliminary survey, permit coordination, system creation, preparation of the SIGA manual book, socialization of SIGA implementation, and evaluation. Evidenced by the increased knowledge of participants in early detection of stunting and other nutritional problems after being given socialization and training. It is recommended for RDS managers to develop RDS as a stunting control center in Kemuning Lor Village by providing more intense socialization and health education to the community.